Local environment characteristics associated with walking and taking transit to shopping districts - Robert James Schneider (Journal of Transport and Land Use)
Mixed logit modeling was used to identify local environment characteristics associated with walking and taking public transit to and from shopping districts. The analysis was based on 388 intercept survey responses and local environment data from 20 San Francisco Bay Area shopping districts. This study makes methodological advances by 1) evaluating an extensive set of explanatory variables (travel time and cost, socioeconomic characteristics, attitudes, perceptions, and local environment characteristics) within the same modeling process and 2) analyzing shopping mode choice within a tour-based framework. Travel time, travel cost, and respondent socioeconomic characteristics had expected relationships with mode choice. Walking to and from shopping districts was associated with shorter trip distances (i.e., shorter travel time relative to other modes). Transit use was associated with shopping district population density and proximity to a transit station. Automobile use was discouraged by higher employment densities and smaller parking lots. The results support strategies such as developing high-density, mixed-use activity hubs; reducing surface parking; and increasing the price of on-street parking to increase walking and taking transit to shopping districts.